Harmonisasi Tiga Lingkungan Pendidikan: Studi Konsep Pendidikan Islam & Kandungan Ayat Al-Qur’an - Abu Warasy Batula; Ahmad Syakir Wildani; Bilqis Nafilah Febrianti; Silvia Siti Rachmawaty; Raka Surya Ramadhan; Muhamad Parhan; Syahidin Syahidin (STIKes Ibnu Sina Ajibarang, 2024)
This research focuses on the crucial role of the Islamic educational environment in supporting an effective educational process. Qualitative methods and literature analysis were employed to delve into this topic. Although the Quran doesn't explicitly address it, Islamic history reveals attention to educational settings like mosques, homes, madrasahs, and universities. In Islam, families hold a primary role in creating an educative atmosphere for children. Preparing parents before forming a family is pivotal in Islamic education, with the concepts of a peaceful, loving, and compassionate family serving as essential foundations. Schools and madrasahs contribute to shaping Islamic character in students, despite the term